GASTROINTESTINAL STROMAL TUMORS: WHAT’S NEW IN THERAPY? - A. G. Kornilova; L. M. Kogoniya; V. S. Mazurin; S. V. Mordanov; О. S. Oksenyuk (Сибирский онкологический журнал)
The literature review is devoted to the analysis of different approaches in the treatment of gastrointestinal stromal tumors since they have been classified as a separate nasological group. The current trends of targeted therapies for gastrointestinal stromal tumors have been presented.